Conservation of centromeric histone 3 interaction partners in plants. (5th May 2020) - Keçeli, Burcu Nur; Jin, Chunlian; Van Damme, Daniel; Geelen, Danny
Abstract : Here we have listed 36 human and yeast CENH3 interaction partners and their corn, rice, and Arabidopsis homologs that are potentially interacting with plant CENH3. Abstract: The loading and maintenance of centromeric histone 3 (CENH3) at the centromere are critical processes ensuring appropriate kinetochore establishment and equivalent segregation of the homologous chromosomes during cell division. CENH3 loss of function is lethal, whereas mutations in the histone fold domain are tolerated and lead to chromosome instability and chromosome elimination in embryos derived from crosses with wild-type pollen. A wide range of proteins in yeast and animals have been reported to interact with CENH3. The histone fold domain-interacting proteins are potentially alternative targets for the engineering of haploid inducer lines, which may be important when CENH3 mutations are not well supported by a given crop. Here, we provide an overview of the corresponding plant orthologs or functional homologs of CENH3-interacting proteins. We also list putative CENH3 post-translational modifications that are also candidate targets for modulating chromosome stability and inheritance.